Users Guide to Ecohydraulic Modelling and Experimentation: Experience of the Ecohydraulic Research Team (PISCES) of the HYDRALAB Network - Frostick, L. E; Thomas, R. E; Johnson, M. F; Rice, S. P; McLelland, S. J (IAHR design manual, 2014)
The internet and world wide web are revolutionizing many aspects of our lives, and have become an accepted part of socioeconomic experience in developed countries. For entertainment, shopping, banking, establishing friendships, seeking information, and so on, the web is the first port of call for an increasing number of people. A few in education have been quick to see the potential of the web as a platform for delivering a variety of teaching and learning materials. Many more, however, would like to make use of the web, but lack either the time or the skills, or both.  Untangled Web provides a guide for those wishing to develop their own teaching and learning resources on the web, whether for local, open or distance learning. By using this book, potential web educators can acquire some of these basic skills and save time by drawing on the experiences of the authors and avoiding the pitfalls and problems that they have encountered. The authors have gained considerable expertise in devising, designing, constructing, testing, adapting and evaluating their own web-based instruction packages which have been developed over a number of years and involve a variety of subject areas. Untangled web is therefore very much focused on practical experience, and while it is primarily aimed at teachers in further and higher education, schoolteachers interested in using the web as a teaching and learning medium will find it useful. Untangled Web has been written by an experienced team from the Department of International Studies at the Nottingham Trent University. David Graham teaches geography and information technology; Jane McNeil is Faculty webmaster and teaches medieval history and information technology; Lloyd Pettiford teaches international relations.Innovative guide to using the web in teaching and learning, providing practical advice for lecturers and teachers on using the web as more than just a support tool.